2019
DOI: 10.1016/j.heliyon.2019.e01640
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Si/Al ratio of high-silica HZSM-5 catalysts on the prins condensation of isobutylene and formaldehyde to isoprene

Abstract: A series of HZSM-5 catalysts with different Si/Al ratio were prepared and characterized with various characteristic methods XRD, BET, NH 3 -TPD, FT-IR spectra of adsorbed pyridine, etc. The effect of Si/Al ratio of HZSM-5 catalysts on the prins condensation of isobutylene and formaldehyde to isoprene was investigated in detail. It is resulted that the catalytic activities are dependent on the acid strength, decreasing with the ratio of Si/Al increases. The optimized catalyst was HZSM-5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a recent study, Yu et al [43] reported similar conclusions. For a series of H-ZSM-5 zeolites, they found that the Si/Al ratio had a crucial impact on zeolite acidity and catalytic performance in isoprene synthesis.…”
Section: Prins Condensantionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a recent study, Yu et al [43] reported similar conclusions. For a series of H-ZSM-5 zeolites, they found that the Si/Al ratio had a crucial impact on zeolite acidity and catalytic performance in isoprene synthesis.…”
Section: Prins Condensantionmentioning
confidence: 56%
“…More recently, Ivanova and coworkers studied this reaction in the presence of H-ZSM-5, H-Beta, H-Y, Zr-Beta, Sn-Beta, and Nb-Beta catalysts [41,42]. Yu et al [43] and Zhu et al [44] used a series of HZSM-5 catalysts with different Si/Al ratio. Vasiliadou et al [45] also used H-ZSM-5 catalysts with various Si/Al ratio, but in a liquid phase process.…”
Section: Prins Condensantionmentioning
confidence: 99%
“…The relative amounts of weak and medium-strong sites were estimated using method of Katada et al [26]. Independently of the sol-gel route, the amount of desor NH3 roughly increased with the Al loading (up to 75 wt% for HSG samples), as repo previously for Ni-Si-Al catalysts prepared via NHSG [17] and silica-alumina mate prepared via HSG [28]. The relative amounts of weak and medium-strong sites were estimated using the method of Katada et al [26].…”
Section: Synthesis and Characterization Of Materialsmentioning
confidence: 63%
“…Numerous studies have been performed to evaluate the performance of liquid and solid acid catalysts in the Prins condensation between FA and MTBE. In the gas–solid reaction operated in a fixed-bed reactor, zeolite, supported phosphate, metal oxide, and supported HPA catalysts , have been studied extensively. As a result of the high working temperature, the catalysts suffer quick deactivation due to the formation of coke.…”
Section: Introductionmentioning
confidence: 99%